Positive Politeness on Strategies of Expressing Apologies by English Department Students of UIN Sunan Gunung Djati Bandung - Wardoyo, Cipto (Buletin Al-Turas, 2017)
This paper tries to describe the strategies of English department students in expressing apologies and their positive politeness strategy while expressing apologies. The data sources are students of UIN Sunan Gunung Djati Bandung, the data are taken by using DCT (Discourse Completion Test). Students of UIN Sunan Gunung Djati use various strategies in expressing apologies when they express apologies to the lecturer for coming late to class; they tend to use IFID followed by the explanation and IFID followed by request. Moreover, when students express an apology to their friends, they use IFID + Promise and IFID+ Explanation. The strategies of expressing apologies to the parent show that the highest number of strategies in expressing apologies by students is IFID+ Explanation and IFID+ Responsibility + Explanation. Positive politeness strategy is performed by students by using the honorific “sir”. On the other hand, positive politeness strategy of expressing apology to a friend, the students use more intimacy words such as “bro, mate, friend”. Students who express an apology to parents tend to use intimacy words such as “Mom, Dad, and Mommy”.Keywords: pragmatics, politeness, speech acts, strategies of expressing apologies. AbstrakPenelitian ini mencoba mendeskripsikan strategi mahasiswa jurusan Bahasa Inggris dalam mengungkapkan permintaan maaf dan strategi kesantunan positif yang digunakan ketika melakukan tindak tutur meminta maaf. Sumber data siswa UIN Sunan Gunung Djati Bandung, datanya diambil dengan menggunakan DCT (Discourse Completion Test). Mahasiswa UIN Sunan Gunung Djati menggunakan berbagai strategi dalam mengungkapkan permintaan maaf. Ketika mereka mengungkapkan permintaan maaf kepada dosen karena datang terlambat mereka dominan menggunakan strategi IFID diikuti dengan penjelasan, dan IFID diikuti oleh permintaan. Ketika mahasiswa menyampaikan permintaan maaf kepada teman, mereka menggunakan IFID + Janji dan IFID + Penjelasan,. Ketika mahasiswa mengungkapkan permintaan maaf mereka lebih banyak menggunakan strategi IFID + penjelasan dan IFID+ tanggungjawab+ penjelasan. Strategi kesantunan positif dilakukan oleh mahasiswa dengan menggunakan kata "sir”. Di sisi lain, strategi kesantunan positif untuk mengekspresikan permintaan maaf kepada teman, para mahasiswa menggunakan kata-kata yang lebih intim seperti "bro, mate, friend", sedangkan ketika dengan orang tua mereka menggunakan “Mom, Dad dan Mommy” Kata kunci: pragmatik, kesantunan, tindak tutur, strategi permintaan maafDOI : 10.15408/bat.v23i2.5786